Le fiasco de la smart city de Google à Toronto - Bernard Fallery (Netcom)
Between utopia and dystopia, the concept of Smart city is in question. The smart city is a dream, but the concrete achievements of capturing behaviors were quickly contested by citizens. The well-documented story of the Google fiasco in 2020 in Toronto illustrates this technological solutionism which envisaged building a platform city, a calculated city. Hyper-connection and algorithmic optimization can then be analyzed at the level of ethics. We can argue that none of the three major ethical principles – that of person, that of duty or that of utility – will be able to found an ethics for digital technology. The inevitable conflicts will not be to be resolved but to be lived, in an ethics based on complex thought.